2022
DOI: 10.1002/pds.5495
|View full text |Cite
|
Sign up to set email alerts
|

Association between opioid therapy trajectories and potential opioid‐related adverse health events

Abstract: Purpose We identified associations between membership in seven group‐based trajectories based on supply of filled opioid prescriptions and potential opioid‐related adverse health events over a 720‐day window. Methods We identified two veteran cohorts with chronic non‐cancer pain who initiated treatment with long‐term opioid therapy between 2008 and 2015, excluding those with prior substance use disorder (n = 373 941) or non‐SUD, opioid‐related adverse outcome (n = 405 631) diagnoses. Outcomes of interest inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 32 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Twenty-four studies were conducted in the United States, 3 were conducted in Canada and 1 was conducted in the United Kingdom. Twenty-one studies 23 , 24 , 40 47 , 50 53 , 55 57 , 59 62 included only patients with chronic noncancer pain, and 7 27 , 28 , 39 , 48 , 49 , 54 , 58 included patients with either chronic noncancer or cancer-related pain. Twenty-two studies enrolled patients with previous or current substance use disorder (median proportion 9%, IQR 4%–13%), 23 , 24 , 27 , 28 , 39 43 , 46 , 48 51 , 53 55 , 57 , 58 , 60 62 and 3 studies excluded patients with comorbid substance use disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four studies were conducted in the United States, 3 were conducted in Canada and 1 was conducted in the United Kingdom. Twenty-one studies 23 , 24 , 40 47 , 50 53 , 55 57 , 59 62 included only patients with chronic noncancer pain, and 7 27 , 28 , 39 , 48 , 49 , 54 , 58 included patients with either chronic noncancer or cancer-related pain. Twenty-two studies enrolled patients with previous or current substance use disorder (median proportion 9%, IQR 4%–13%), 23 , 24 , 27 , 28 , 39 43 , 46 , 48 51 , 53 55 , 57 , 58 , 60 62 and 3 studies excluded patients with comorbid substance use disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies 23 , 24 , 40 47 , 50 53 , 55 57 , 59 62 included only patients with chronic noncancer pain, and 7 27 , 28 , 39 , 48 , 49 , 54 , 58 included patients with either chronic noncancer or cancer-related pain. Twenty-two studies enrolled patients with previous or current substance use disorder (median proportion 9%, IQR 4%–13%), 23 , 24 , 27 , 28 , 39 43 , 46 , 48 51 , 53 55 , 57 , 58 , 60 62 and 3 studies excluded patients with comorbid substance use disorder. 45 , 52 , 56 Twenty-three studies included patients with comorbid mental illness (median proportion 31%, IQR 20%–41%), 23 , 24 , 27 , 28 , 40 42 , 45 49 , 51 58 , 60 62 and 5 studies exclusively recruited veterans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of people 65 years or older with CNCP and new opioid use found that individuals with increasing or consistent opioid dose trajectories had a higher risk of opioid-related adverse events than those with decreasing opioid dose trajectories . Similarly, studies examining opioid use among US veterans identified higher risk of opioid-related adverse events, hospitalization, and all-cause mortality among high use and increasing use groups . Improved understanding of the characteristics of individuals with higher use trajectories could benefit clinicians who initiate opioid therapy, providing information to support monitoring and interventions to prevent future problems as well as assisting with improved targeting of resource-limited interventions where they are most likely to be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…32 Tapering opioids (sometimes called "deprescribing") has been identified as a key strategy in improving pain and reducing opioidrelated harms in patients using opioids for pain outside the context of active malignancy or palliation. 20,24,49 The 2010 Canadian Guideline for Safe and Effective use of Opioids for Chronic Noncancer Pain and the 2016 Centers for Disease Control and Prevention Guideline for Prescribing Opioids for Chronic Pain were updated in 2017 and 2022, respectively, both with greater communication around safe and effective deprescribing of opioids. 7,15,17,21 In Australia, a National Health and Medical Research Council (NHMRC) endorsed Evidence-Based Clinical Practice Guideline for Deprescribing Opioid Analgesics was published in September 2022 to guide clinicians on when and how to taper opioids.…”
Section: Introductionmentioning
confidence: 99%